2021
DOI: 10.1002/cssc.202101161
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photovoltaic Performance of BiSCl Solar Cells Through Nanorod Array

Abstract: BiSCl single‐crystalline nanofibers were synthesized by a facile one‐pot solvothermal approach for the first time. BiSCl possesses a double chain type structure and grows readily along the c‐axis, resulting the fibrous morphology. UV/Vis absorption spectroscopy revealed that BiSCl nanofibers exhibit a strong light absorption in a wavelength range from UV to visible light, corresponding to a bandgap of 1.96 eV. Ultraviolet photoelectron spectroscopy and density functional theory calculations revealed that BiSCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…[51,52] These findings set the colloidal BiEX NCs as promising solar absorbers for photocatalytic and optoelectronic applications. [23,53,54] This work thus extends our knowledge on the chemistry of metal chalcohalide nanomaterials and contributes to establish this class of inorganic semiconductors as an effective complement to metal chalcogenides and halides for light-harvesting purposes.…”
Section: Discussionmentioning
confidence: 56%
“…[51,52] These findings set the colloidal BiEX NCs as promising solar absorbers for photocatalytic and optoelectronic applications. [23,53,54] This work thus extends our knowledge on the chemistry of metal chalcohalide nanomaterials and contributes to establish this class of inorganic semiconductors as an effective complement to metal chalcogenides and halides for light-harvesting purposes.…”
Section: Discussionmentioning
confidence: 56%
“…[22][23][24] Many procedures have been reported for the synthesis of pnictogen chalcohalides such as growth from melts, 25 gas phase reaction, 26 and solvothermal methods. 17,27 These methods often require high temperatures, lengthy reaction times, or the use of toxic H 2 S gas for sulfurization. Therefore, a relatively low-temperature, robust, and facile synthesis method for metal chalcohalides is required.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth chalcohalides with excellent physical and unique chemical structures exhibited an easy-totune band structure and received extensive attention in photocatalytic applications in the last few years. [18][19][20][21] Wu et al 22 prepared single-crystalline Bi 19 Cl 3 S 27 nanorods by a simple solvothermal method and the photocatalytic results showed that the nanorods had high activity in the photocatalytic removal of Cr(VI). The Bi .333 (Bi 6 S 9 )Br semiconductor nanorods have been prepared by facile hydrothermal route.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, photocatalysts with negative E CB position were directly synthesized without any modification will be promising. Bismuth chalcohalides with excellent physical and unique chemical structures exhibited an easy‐to‐tune band structure and received extensive attention in photocatalytic applications in the last few years 18‐21 . Wu et al 22 prepared single‐crystalline Bi 19 Cl 3 S 27 nanorods by a simple solvothermal method and the photocatalytic results showed that the nanorods had high activity in the photocatalytic removal of Cr(VI).…”
Section: Introductionmentioning
confidence: 99%